On the role of the verb phrase in English sentence structures (through contrastive analysis with Vietnamese) - Trần Hữu Phúc.; Trần Hữu Mạnh, Assoc.prof.Dr. (Hà Nội : Đại học Ngoại ngữ Hà Nội, 1998)
This thesis presents the role of the verb phrase in English sentence structures through contrastive analysis with Vietnamese.
Keywords: Anh ngữ; Grammar; Verb phrase; English thesis; Luận văn Anh ngữ; English Sentence structures; English linguistics -- Grammar